Strategi Penyiapan Lulusan Unggulan di Pondok Pesantren Sabilul Muttaqin Karanganyar Kraton Pasuruan - Tarwichatul Jadidah; Abdul Aziz; Mulyono (EduInovasi: Journal of Basic Educational Studies, 2025)
The objective of this study is to explain the graduate competencies of Pesantren Sabilul Muttaqin Karanganyar Kraton Pasuruan, to reveal the strategies used in preparing its graduates, and to describe the evaluation process of its graduates. This research employs a qualitative approach, with the researcher acting as an observational participant. Data collection techniques include interviews, observations, and documentation. The data analysis process consists of data verification, classification, interpretation, and conclusion drawing. The graduate competencies consist of: a). Academic Competence, which includes (1) the results of Imda (mid-term exams) and Imni (final exams), (2) Qur’an reading tests including ghoroib recitation, and (3) the results of Upramer (Teaching Practice Examination). b). Non-Academic Competence, which is assessed through students’ attitudes and behavior during their one-year period of service as assistant administrators at the pesantren, as well as disciplinary records from the Indisciplinary Book. The strategies for preparing graduates include: a). Requiring all Tsanawiyah level students to participate in extracurricular activities beyond the standard madrasah program, b). Conducting socialization sessions by the Department of Tasked Teachers (UGT) for third-year Tsanawiyah students in the month of Dzul Qo’dah through the distribution of questionnaires to determine their voluntary readiness to participate in the Guru Tugas program, c). Implementing intensive training and development programs. The evaluation process is conducted in three areas: a). Academic Evaluation, based on report card grades, Qur’anic reading test results, and Upramer scores, b). Non-Academic Evaluation, coordinated between the UGT administrators and pesantren leadership by assessing the students’ ḥāliyyah (daily conduct and character) during their service period, and reviewing entries in the disciplinary record book, c). On-Site Assignment Evaluation, which is carried out periodically through (1) monthly evaluations using a Google Form filled out by both the Tasked Teacher (GT) and the Tasked Teacher Supervisor (PJGT) as a two-way evaluation instrument, and (2) biannual evaluation meetings with PJGTs held in the months of Rabi' al-Awwal and Sha'ban.